Pemberdayaan Ibu-Ibu Santri Yatim dalam Menjalankan UMKM Toko Online Melalui Media Digital - Kussusanti, Kussusanti; Hasna, Safira; Nur Ayu, Meta (LPkM Universitas Bakrie, 2024)
One of the members of the community who needs empowerment is the mothers of orphaned students. As single parents, they find it challenging to financially support their children, especially considering their low level of education and skills. If finding employment in a company is difficult, one solution that can be pursued is to start a Micro, Small, and Medium-sized Enterprise (MSME). With the advancements in current technology, one feasible option is to establish an online store. However, their skills in online business are still quite limited. Therefore, training in this field is essential, covering marketing strategies, marketing management, food photography, and online selling techniques. This community service program aimed at one of the foundations that support orphaned students and foster children, as well as nurture their mothers, namely the Orphanage Foundation of Pejaten (YYPP). The method used involves face-to-face offline training, workshops for direct practice, monitoring and mentoring, until the participants are capable of running an online store proficiently. The pre-test and post-test results show that participants' knowledge about social media changed from 77% to 100%, knowledge about product branding changed from 8% to 85%, knowledge about photography changed from 31% to 92%, and knowledge about online sales changed from 23% to 85%. The participants expressed satisfaction, especially in terms of delivering content. 85% of participants stated that they strongly agreed that program was presented effectively by the speakers.